A fuzzy inference model for risk based informed decision-making in e-business - Hussain, Omar; Dillon, Tharam S.; Chang, Elizabeth; Hussain, Farookh Khadeer (IEEE Computer Society, 2009)
Since its invention, the web has considerably advanced and it now provides its users with sophisticated technologies and processes for facilitating interactions. This has enabled its users to complete their tasks by efficient ways, which reduces the duration of their interaction/s and in turn increases their productivity. But in such an environment, it is imperative for a user to make informed decisions in a proactive way by which it can achieve its aims and maximize its interaction experience. In the literature, various approaches have been proposed which a user can consider and utilize while making an interaction-based decision in web-based ecommerce. But at the same time the notion of risk has been considerably ignored in that domain; even though it has been mentioned in the literature that risk plays an important part while decision-making in any domain. So in order to have such an analysis of risk while decision-making, in this paper we highlight the importance of risk and then propose a fuzzy inference model for assisting risk-based decision making in e-commerce business interactions.